Every birth is a story: process of choosing the route of delivery - Virgínia Junqueira Oliveira; Claudia Maria de Mattos Penna
ABSTRACT Objective: To analyze the discourses on the choice of the route of delivery from the perspective of women and health professionals in a public network. Method: The methodological approach is the discourse analysis. The data collection was through interviews and the treatment of the data was based on discourse analysis. Results: The categories were: 1- Between the preference and the decision there is no choice; 2- The complexity of the choice of the route of delivery; 3- It is necessary to legitimize the choice of the woman. Final considerations: From the perspective of women in labor the route of delivery is determined by the physician and women are not proactive. The nurses' performance is timid, although their presence is fundamental for stimulating the physiological delivery and promoting the autonomy of women. It identifies the need for the physician to adopt a welcoming attitude, informing the women about the pros and cons involved in choosing the route of delivery.